Bacterial Patterns and Sensitivity to Antibiotics in Neonatorum Sepsis Patients at Dr. M. Djamil Padang General Hospital in the Period 2018–2021 - Fenty Primadhani; Linosefa, Linosefa; Fitrisia Amelin; Almurdi, Almurdi; Elly Usman; Rahmi Lestari (Sean Institute, 2025)
Neonatal sepsis is one of the leading causes of morbidity and mortality in neonates. Bacteria are the most common cause of neonatal sepsis. The appropriate empirical therapy is given based on the bacterial pattern and sensitivity at the site. The appropriate use of empirical antibiotics can help reduce the neonatal mortality rate. This study aimed to evaluate bacterial patterns and antibiotic sensitivity in neonatal sepsis patients at RSUP Dr. M. Djamil Padang period 2018-2021. This study is a descriptive study that used a total sampling method with 63 samples that met the inclusion criteria. The results showed that neonatal sepsis was most commonly found in neonates aged 4-28 days, which were mostly male, had a birth weight < 2500 grams, had a mortality rate of 25.4%, and neonatal pneumonia was the most comorbid disease. The most common causative bacteria were Klebsiella pneumoniae and Staphylococcus haemolyticus. Klebsiella pneumoniae is sensitive to amikacin, tigecycline, meropenem, and ertapenem. Staphylococcus haemolyticus was sensitive to tigecycline, nitrofurantoin, vancomycin, linezolid, and quinupristin / dalfopristin. This study concluded that the most common bacteria causing neonatal sepsis were Klebsiella pneumoniae and Staphylococcus haemolyticus. Klebsiella pneumoniae was sensitive to amikacin, tigecycline, meropenem, and ertapenem. Staphylococcus haemolyticus was sensitive to tigecycline, nitrofurantoin, vancomycin, linezolid, and quinupristin / dalfopristin. Clinicians are expected to review the clinical practice guidelines for neonatal sepsis to suit bacterial patterns and their sensitivity to antibiotics.